Pharmacokinetic and pharmacodynamic studies of pregabalin suppositories based on pharmacological research. (4th December 2018) - Yajima, Ryo; Matsumoto, Kazuaki; Yokono, Kanako; Watabe, Yuki; Enoki, Yuki; Taguchi, Kazuaki; Ise, Yuya; Katayama, Shiro; Kizu, Junko
Abstract: Objectives: As commercially available pregabalin preparations are limited to oral administration, it is impossible to use it as an adjuvant analgesic for neuropathic cancer-related pain in terminally ill cancer patients with oral feeding difficulties. The objective of this study was to develop a pregabalin suppository to be available at hospitals. Methods: Pregabalin suppositories were prepared using bases comprising six different compositions of Witepsol H-15, Witepsol S-55, and Witepsol E-75. The suppository release test and stability test were performed in vitro . The pharmacokinetics and pharmacodynamics of the suppositories were assessed in rats. Key findings: In the in vitro releasing test, the pregabalin suppositories with H-15, H-15 : S-55 = 1 : 1, H-15 : S-55 = 2 : 1, H-15 : S-55 = 1 : 2 released approximately 100% of the pregabalin within 180 min. Among these pregabalin suppositories, only the suppository with H-15 : S-55 = 2 : 1 demonstrated an equivalent AUC0−∞ with the oral administration group. Consistent with the results of the pharmacokinetic study, the pregabalin suppository with H-15 : S-55 = 2 : 1 exhibited antinociceptive effects. In addition, the pregabalin suppository with H-15 : S-55 = 2 : 1 was stable for 12 weeks when refrigerated with light shielding. Conclusions: The pregabalin suppositories prepared in this study may be applicable for pain control for terminally cancer ill patients with oral feeding difficulties.